Sustainable agriculture and responsible use of pesticides: commercial crop cultivators’ knowledge, attitudes, and practice perspectives regarding pesticide use - Udayanga, Samitha; Bellanthudawa, B. K. A.; De Zoysa, H. L. S. (Frontiers in Sustainable Food Systems, 2024)
The excessive use of pesticides has been identified as a main barrier to sustainable agriculture in the developing countries, that can lead to several negative consequences, posing a significant threat to the total environment. Therefore, the present study investigated the informedness of smallholder vegetable farmers on responsible use of pesticides, exploring how their knowledge, attitudes and protective practices (KAP) are associated with the safe use of pesticides. A questionnaire survey was conducted with 206 smallholder farmers in the central highlands of Sri Lanka to identify how KAP are associated with responsible use of pesticides. Secondly, two focus group discussion were conducted to gain insights into the farmers’ awareness of the responsible use of pesticides. The analysis reveals an overall deficiency in informedness about responsible pesticide use, primarily stemming from moderate level of knowledge and perceptions related to protective practices. Furthermore, farmers tend to face constraints due to limited access to information on responsible use of pesticides and a heavy reliance on pesticides, believing pesticides to be a primary means of increasing crops. Results also indicate a significant association between knowledge, practice, and informedness, whereas attitudes did not significantly contribute to informedness. Significant disparities in informedness were identified among different demographic groups, with men and younger farmers exhibiting higher levels of awareness. Thus, we suggest that farmers’ informedness can be improved by targeted efforts to enhance their knowledge and correct misconceptions on the use of pesticides.